2015
DOI: 10.5232/ricyde2015.04207
|View full text |Cite
|
Sign up to set email alerts
|

The effects of various visual conditions on the gait cycle in children with different level of motor coordination-a pilot study. [Cómo afectan diferentes condiciones visuales a la marcha en niños con diferente nivel de coordinación motriz- un studio piloto].

Abstract: The importance of vision and the visual control of movement have been addressed in the literature related to motor control. Many studies have demonstrated that children with low motor competence in comparison to their typically developing peers may rely more heavily on vision to perform movements. The aim of the study was to highlight the effects of different visual conditions on motor performance during walking in children with different levels of motor coordination. Participants (n=8, Mean age = 8.5±.5 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…These tests characterize the coordination of movements of different parts of the body and the accuracy of throws. These data supplement the results of Agricola et al [11] and Palomo-Nieto et al [12] on the importance of coordinating movements of various parts of the body in assessing the coordination abilities of children and adolescents. The given data confirm conclusions of Ivashchenko O.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These tests characterize the coordination of movements of different parts of the body and the accuracy of throws. These data supplement the results of Agricola et al [11] and Palomo-Nieto et al [12] on the importance of coordinating movements of various parts of the body in assessing the coordination abilities of children and adolescents. The given data confirm conclusions of Ivashchenko O.…”
Section: Discussionsupporting
confidence: 88%
“…• on the influence of visual perception on the coordination of movements of various parts of the body of children [11,12];…”
Section: Introductionmentioning
confidence: 99%
“…After having carried out the research, it has been observed that within the physical education classroom, there is a percentage of 18.8% of students with motor competence problems, as Cratty (1982) cites, who states that between 10 and 20 percent of schoolchildren develop some type of motor clumsiness. This percetage also has been seed in studies by Palomo, Psotta, Agricola, Abdollahipour, & Valtr (2015) or Ruiz, Rioja, Graupera, Palomo, & Garcíal (2015).…”
Section: Motor Problems In Physical Education Classsupporting
confidence: 58%
“…• Agricola et al (2015), Palomo-Nieto et al (2015 on the importance of movement coordination of different parts of the body in evaluating children's and adolescents' coordination abilities; • Volkov, and Nagovitsyn (2018) about the influence of motor activity and purposeful usage of physical education means on a positive dynamics of movement coordination development in children and adolescents; • Meadmore, Exell, Burridge, Hughes, Freeman, and Benson (2018) on the gender differences in children related to the body composition and movement coordination. During the analysis, the study confirmed Ivashchenko's (2016) conclusions as to the usage of factor analysis for the evaluation of the current state of motor preparedness, and the usage of discriminant analysis for the evaluation of the state dynamics in the age range, which makes it possible to determine informative indicators for a comprehensive control of motor preparedness.…”
Section: Discussionmentioning
confidence: 99%
“…• the influence of movement coordination level on building motor skills in schoolchildren (Khudolii, Ivashchenko, & Chernenko, 2015;Ivashchenko, 2016;Kapkan, 2015); • the interrelation of anthropometric, motor and cognitive abilities in children (Iadreev, Cherkashin, Vujkov, & Drid, 2015;Novak, Podnar, Emeljanovas, & Marttinen, 2015); • the relationship between the body mass index, subcutaneous fat and the manifestation of movement coordination in children aged 11-14 (Drid, Vujkov, Jaksic, Trivic, Marinkovic, &Bala, 2013;Han, A., Fu, A., Cobley, S., & Sanders R. H., 2017); • the influence of visual perception on children's movement coordination of different parts of the body Palomo-Nieto, Psotta, Agricola, Abdollahipour, & Valtr, 2015); • the effect of physical activity modes on the plasticity of motor skills in schoolchildren (Hadžić, Bjelica, Vujović, & Popović, 2015;Khudolii, & Ivashchenko, 2014). When studying the structure of schoolchildren's motor preparedness, it is effective to use multidimensional methods of mathematical statistics, such as factor and discriminant analyses (Ivashchenko, 2016;Lopatiev, Ivashchenko, Khudolii, Pjanylo, Chernenko, & Yermakova, 2017).…”
Section: Introductionmentioning
confidence: 99%